MENAKAR MINAT MAHASISWA UNIVERSITAS PUTERA BATAM PADA PENGGUNAAN PRODUK TEKNOLOGI FINANSIAL - mortigor afrizal purba (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
The aim of this reserch is to find out how much the level of financial literacy in Universitas Putera Batam students and to find out whether or not the influence of the level of financial literacy and promotion strategies through social media to the interest of using technology financial products. The type of this research is a quantitative research using probability random sampling technique, the respondents are the students of accounting, management, others study program. The data collection in this study used a questionnaire method with a Likert scale model and distributed to 100 respondents. In this study the data analysis that used is descriptive analysis, simple regression analysis and multiple regression analysis using SPSS 22.0.The results of this study showed that (1) the level of financial literacy in the fourth student of the study program belongs to the category of sufficient literate or is still fairly categorized with a percentage of 81.12 percent. (2) There is a positive and significant influence between financial literacy variables on the interest in using technology financial products. (3) There is a positive and significant influence between the variables of promotional strategies through social media on the interest in using technology financial products. (4) There is a positive and significant influence between financial literacy variables and promotion strategies through social media on the interest in using technology financial products. This illustrates that the interest of students of Universitas Putera Batam to use financial technology products is very satisfying category. Keywords: Financial Literacy, Promotion Strategy, Interest.